Revisiting the Annual Incidence of Type 1 Diabetes Mellitus in Children from the Southeastern Anatolian Region of Turkey: A Regional Report - Şervan Özalkak; Ruken Yıldırım; Selma Tunç; Edip Ünal; Funda Feryal Taş; Hüseyin Demirbilek; Mehmet Nuri Özbek (Galenos Yayincilik, 2022)
INTRODUCTION: Objective: The incidence of type 1 diabetes mellitus (T1D) in children has an increasing trend globally, with a variable rate depending on region and ethnicity. Our group first reported T1D incidence in Diyarbakır in 2011. The aim of this study was to evaluate the current incidence rate of pediatric T1D in Diyarbakır, and compare the incidence, and clinical and presenting characteristics of more recent cases with those reported in our first report. METHODS: Methods: Hospital records of patients diagnosed with T1D in Diyarbakır city between 1st January 2020 and 31st December 2020 and aged under 18 years old were retrieved, and their medical data was extracted. Demographic population data were obtained from address-based census records of the Turkish Statistical Institution (TSI). RESULTS: Results: Fifty-seven children and adolescents were diagnosed with T1D. Of those, 34 were female (59.6%), indicating a male/female ratio of 1.47. The mean age at diagnosis was 9.5±3.9 years (0.8-17.9). TSI data indicated a population count of 709,803 for the 0-18 years age group. Thus the T1D incidence was 8.03/105 in the 0-18 age group and was higher in the 0-14 age group at 9.14/105. The cumulative increase in the incidence of T1D in the 0-14 age group was 26.9% suggesting an increasing rate of 2.7% per year. The frequency of presentation with diabetic ketoacidosis was 64.9%. DISCUSSION AND CONCLUSION: Conclusion: The annual incidence of pediatric T1D in Diyarbakır city increased from 7.2/105 to 9.14/105 within the last decade. The rate of annual increase was 2.7% in the 0-14 age group comparing this study with our earlier report, with a predominance in male subjects and a shift of peak incidence from the 5-9 year age group in the first study to the 10-14 year age group in this one.